Auditing Research: Issues and Opportunities (Book). - Barrett, Michael J. (The Accounting Review, 1984)
Reviews the book "Auditing Research: Issues and Opportunities," edited by Anthony G. Hopwood, Michael Bromwich and Jack Shaw.